Entropy optimized MHD nanomaterial flow subject to variable thicked surface - Wang, Jing; Muhammad, Riaz; Khan, M. Ijaz; Khan, W.A.; Abbas, S.Z. (Computer methods and programs in biomedicine, 2020)
•Here entropy generation in viscous fluid flow over a variable thicked surface is addressed.•Electrical conducting fluid is considered.•Heat generation/absorption, dissipation and Joule heating effects are considered.•Brownian and thermophoresis diffusion effects are further accounted. Here we investigate the irreversibility aspects in magnetohydrodynamics flow of viscous nanofluid by a variable thicked surface. Viscous dissipation, Joule heating and heat generation/absorption in energy expression is considered. Behavior of Brownian diffusion and thermophoresis are also discussed. The nanoliquid is considered electrical conducting under the behavior of magnetic field exerted transverse to the sheet. Using similarity variables the nonlinear PDEs are altered to ordinary one. The obtained system are computed through Newton built in shooting method. Significant behavior of various involving parameters on entropy generation rate, velocity, concentration, Bejan number and temperature are examined. Gradient of velocity and heat transfer rate are numerically computed through tabulated form. Velocity field is augmented versus power index (n). Temperature and velocity profiles have opposite characteristics for larger approximation of Hartmann number. Concentration profile has similar impact against Brownian diffusion variable and Lewis number. Entropy optimization is boost up via rising values of Brinkman and Hartmann numbers. Bejan number is declined for increasing value of Hartmann number.